2016
DOI: 10.17988/0198-7429-41.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Setting Interventions for Students with Behavior Problems: A Systematic Review

Abstract: Students with persistent behavior problems, including those with or at risk for emotional or behavioral disorders, often struggle to be self-regulated learners. To improve self-regulation skills, numerous strategies have been suggested, including goal setting. Whereas goal setting has focused mostly on academic and life skills, behavioral goal setting has received less attention, particularly in terms of determining best practices for effective goal setting in school-based interventions. Thus, the purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 70 publications
(133 reference statements)
7
48
0
Order By: Relevance
“…Therefore, the training or intervention is more targeted. Previous intervention studies have found that appropriate intervention goals can have a good effect ( Dunford, 2011 ; Bruhn et al, 2016 ; Vroland-Nordstrand et al, 2017 ; Yang et al, 2019 ). The reason for this study’s good intervention effect is that the intervention goals were aimed at improving the undercontrollers’ externalizing problem behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the training or intervention is more targeted. Previous intervention studies have found that appropriate intervention goals can have a good effect ( Dunford, 2011 ; Bruhn et al, 2016 ; Vroland-Nordstrand et al, 2017 ; Yang et al, 2019 ). The reason for this study’s good intervention effect is that the intervention goals were aimed at improving the undercontrollers’ externalizing problem behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…According to Locke and Latham (2006), the number of discoveries made is without limit because goal-setting is an open theory. In their overview of goal-setting instruction for students with behavioral problems, Bruhn et al (2016) found that, in most cases, students set goals based on their present levels. Therefore, instructors need to pay particular attention to whether learners need to set a new goal.…”
Section: Discussionmentioning
confidence: 99%
“…This positive behavior change led many individuals to set new goals . An increase in self‐esteem and satisfaction were reported as consequences of goal setting as well. Ntoumanis et al noted that athletes who set goals had an increase in self‐esteem, where Furze reported that self‐esteem increased in those with chronic disease who set and attained the goals.…”
Section: Definition and Uses Of The Conceptmentioning
confidence: 99%
“…Mento et al ascertained that when employees set goals on their own, they reported a sense of satisfaction when goals were met. In addition, Bruhn et al reported that students who set academic goals reported being more satisfied with their academic performance than those students who did not set academic goals. Two other consequences, a sense of pride and a feeling of being energized, was noted by Locke and Latham and Shalley in individuals who set goals.…”
Section: Definition and Uses Of The Conceptmentioning
confidence: 99%